King Hussein and the challenge of Arab radicalism : Jordan, 1955-1967 - Oxford University Press; Dana, Uriel; editor (New York : Oxford University Press, 1989)
In cooperation with the Moshe Dayan Center for Middle Eastern and African Studies, Tel-Aviv University
Keywords: Arab Countries -- Foreign relations -- Jordan; Hussein, King of Jordan, 1935.; Jordan -- Foreign Relations -- Arab Countries; Jordan -- Politics and government